Pendayagunaan Zakat Produktif Dalam Pemberdayaan Ekonomi Umat Menurut Yusuf Qardhawi - Nur Iqbal, Muhammad (Jurnal Landraad, 2022)
Yusuf Qaradhawi has engaged in a considerable amount of innovative ijtihad, previously unseen in classical texts. As a result, his thoughts are genuinely proportional in positioning zakat as an Islamic legal doctrine capable of realizing justice and social welfare, especially in the modern era. One notable aspect of his ijtihad is productive zakat. Therefore, this research aims to examine Yusuf Qaradhawi's thoughts that place serious emphasis on the economic empowerment of the community through productive zakat. This study employs a literature review method within the framework of legal research, utilizing a qualitative approach. The research findings indicate that the utilization of zakat funds, whether for consumptive or productive recipients, needs to consider factors of equal distribution and parity. In addition to these factors, attention should be given to the actual needs of zakat recipients, the capacity of zakat funds, and the conditions of the recipients themselves, leading to an improvement in welfare. Specifically for productive recipients, the use of zakat funds should be directed towards transforming them from zakat recipients to zakat contributors (muzakki). Managing productive zakat requires an effective mechanism/system to monitor and promptly address fund misappropriation or other challenges during its implementation. The proposed model for managing productive zakat includes the Surplus Zakat Budget, In Kind, and Revolving Fund.